The role of antenatal corticosteroids in twin pregnancy - Zhu, Jie; Li, Shuyue; Zhao, Ying; Xiong, Yu (Frontiers in Pharmacology, 2023)
Twin pregnancy was associated with significantly higher rates of adverse neonatal and perinatal outcomes. One of the underlying causes is that twins are prone to preterm birth. Antenatal corticosteroids are widely used for reducing the incidence of neonatal respiratory distress syndrome initially and other neonatal mortality and morbidities subsequently. As it is widely used as a prophylactic treatment for potential premature births, there remain controversies of issues relating to twin gestations, including window for opportunity, timing of use, repeat course, optimal administration-to-delivery intervals, dosage, and type of corticosteroid. Thus, we present a thorough review of antenatal corticosteroids usage in twin gestation, emphasizing the aforementioned issues and attempting to offer direction for future investigation and clinical practice.